Stereotype threat and older worker’s attitudes: a mediation model - Oliveira, Eduardo (2018)
Porpose - Taking a social identity approach, the purpose of this paper is to examine the extent to which age-based stereotype threat mediates the relationships between older workers’ negative age-based metastereotypes and two negative work attitudes: organizational disidentification and work disengagement. Design/methodology/approach - A two-wave cross-sectional design was adopted to collect data from 423 blue-collar older workers of the Portuguese manufacturing sector. Structural equation modeling was used to test the mediation model. Findings-The analyses show that age-based stereotype threat partially mediates the relationship between negative age-based metastereotypes and negative work attitudes. Moreover, findings suggest that older workers respond to negative age-based metastereotypes through threat reactions, and undesirable work attitudes. Originality/value-This paper contributes to the literature by showing the importance of negative age-based metastereotypes and age-based stereotype threat in workplace dynamics. It also provides evidence that age threats impair the relationship older workers keep with their organization and their work.